The (un)intended consequences of Lionel Robbins Essay in the Prehistory of Microfoundations - Thiago Dumont Oliveira (2016)
Robbins belongs to the prehistory of microfoundations, for his definition of economics helped to buttress the centrality that individual choice acquired after the Second World War. This, however, was an unintended effect of his seminal work An Essay on the Nature and Significance of Economic Science. Our claim is that, underlying his definition ofeconomics, a novel approach to methodological individualism is advanced, in which the isolated individual plays the role of a temporary device. The economic man is but a first step in order to analyse more complex social phenomena. More specifically, three types of methodological individualism are outlined and it is argued that Robbins approach cannot be classified as any of them; we thus propose a different category, that of first-step individualism. Robbins rationale for focusing on the isolated individual is not that social phenomena can be reduced to individual behaviour, but rather that this is the best startingpoint for economics, if it is to progress and be able to deal with more complex phenomena in the future. Robbins participation in the Economic Advisory Council, in 1930, shed some light on Robbins overarching interest on the interplay of economics as a science and political economy as a broader field that includes normative considerations. This rendersinvalid criticisms related to the absence of ethical considerations in Robbins approach to economics. Thus, the Essay should be situated within his larger purpose of illuminating the extent to which the science of economics could serve as an important tool necessary, though not sufficient to orient the formulation of public policies.